RANCANG BANGUN ALAT PELEPAS SEAL POWER STEERING PADA MOBIL TOYOTA HILUX - epriyandi, epriyandi (Pengelola Jurnal Politeknik Negeri Ketapang, 2023)
In general, most workshops still use manual methods to remove the power steering seal, so the processing time for removing the power steering seal will take around 1 hour. So that the work of removing the power steering seal is faster and more precise so that it is more effective and efficient, a power steering seal removal tool is needed to make the job easier. Based on the problems above, it is deemed necessary to make tools to assist in removing the power steering seal on Toyota Hilux cars. Making the power steering seal removal tool requires selecting the right materials, so that this tool is able to work optimally, and the operation is very simple so that everyone can use this tool. This tool is made using ST37 steel with a strength of 37 Kg/mm2. St37 iron is easy to get and the price is relatively cheap. This power steering seal removal tool consists of various components that support each other so that it can work properly. Some components of the power steering seal removal tool are threads, nuts and iron bars. Based on the test results after the manufacturing process is carried out, using this seal removal tool only takes 2 minutes, whereas if removing the seal using the manual method it will take 1 hour. The seal has a high potential for damage if the seal is removed using a manual method. But if you use this seal removal tool, the seal will not be damaged.